PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND TABLE UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN IKATAN KIMIA DIKELAS X MIA SMA NEGERI 12 PEKANBARU - Lislidiawati, Nopa Lislidiawati; Rery, R Usman Rery; ', Rini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Research on the implementation of cooperative learning model type round table to increase learning achievement has been done on the subject of the rate of reaction in class X SMAN 12 pekanbaru.  This research is a kind of experiment research with pretest-posttest design. The research was conducted in SMAN 12 pekanbaru The samples of this research were the students of class X MIA 3 as the experimental class and  students of class XI MIA 4 as  the control class. Experimental class is a class that is applied model of cooperative learning type round table, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 2,60> 1,68, means that the application of model cooperative learning type round table can improve student achievement on the subject of the rates of reaction in class X MIA SMAN 12 pekanbaru. Key Words: Cooperative Learning type Round Table, Learning Achievement.